APEXIFICATION ON PERMANENT MOLAR OF NINE-YEAR-OLD PATIENT - Febriyanti Febriyanti; Sri Hartini Soemartono (Faculty of Dentistry, Universitas Indonesia, 2006)
Apexification is the preparation of the endodontic treatment for a tooth with pulpal necrosis and incompletely developed apex. The aim of this treatment is to stimulate further apex development and formation of calcified tissue at the apex, so that conventional endodontic treatment could be performed. One of the most suitable material apexification is calcium hydroxide since it has an biocompatibility, antimicrobial property, and ability to stimulate hard tissue formation. In this case apexification was performed on a 9 year-old boy with incompletely developed apex and necrotic 36 tooth. There are no subjective or clinical symptoms after 6 months. Although in the radiograph, apical closure was not clearly detected, apical stop was obtained in clinical examination. Subsequently, the 36 tooth was restored with onlay.